Optically coupled cavities for wavelength switching - Costanzo Caso, Pablo Alejandro (2011)
An optical bistable device which presents hysteresis behavior is proposed and experimentally demonstrated. The system finds applications in wavelength switching, pulse reshaping and optical bistability. It is based on two optically coupled cavities named master and slave. Each cavity includes a semiconductor optical amplifier (SOA), acting as the gain medium of the laser, and two pair of fiber Bragg gratings (FBG) which define the lasing wavelength (being different in each cavity). Finally, a variable optical coupler (VOC) is employed to couple both cavities. Experimental characterization of the system performance is made analyzing the effects of the coupling coefficient between the two cavities and the driving current in each SOA. The properties of the hysteretic bistable curve and switching can be controlled by adjusting these parameters and the loss in the cavities. By selecting the output wavelength (λ1 or λ2) with an external filter it is possible to choose either the invert or non-invert switched signal. Experiments were developed employing both optical discrete components and a photonic integrated circuit. They show that for 8 m-long cavities the maximum switching frequency is about 500 KHz, and for 4 m-long cavities a minimum rise-time about 21 ns was measured. The switching time can be reduced by shortening the cavity lengths and using photonic integrated circuits.